Pengaruh Model Project Based Learning Terhadap Hasil Belajar Kognitif Larutan Penyangga - Nur Fadillah Safaruddin; La Rudi; Fahyuddin (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2024)
This study aims to examine the effect of the Project Based Learning model used in learning buffer solution material and determine student responses to the Project Based Learning model that has been applied. Type of research: experimental. Research design: pretest posttest control group design. Research instruments: learning outcomes test (pretest postest) and student response questionnaire. Research subjects: students of grade XI MIPA 1 and XI MIPA 2. Data analysis techniques: quantitative data analysis, descriptive and inferential. The results of the study: there were differences in cognitive learning outcomes in the experimental class and the control class. This is due to the difference in learning models used, while the experimental class uses a project-based learning model which makes students more active and learning outcomes increase compared to the control class that uses a problem-based learning model.